2014
DOI: 10.3109/07420528.2013.846350
|View full text |Cite
|
Sign up to set email alerts
|

Differences in circadian patterns between rural and urban populations: An epidemiological study in countryside

Abstract: The physiological pattern of the sleep-wake cycle is influenced by external synchronizing agents such as light and social patterns, creating variations in each individual's preferred active and sleep periods. Because of the demands of a 24-h working society, it may be imperative for many people to adapt their sleep patterns (physiologically) to their daily activities. Therefore, we analyzed the difference in sleep patterns and chronobiological parameters between an essentially rural farming and urban small-tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…This rural increase has been found in France [6], Hungary [48], New Zealand [49], Sweden [49], and Austria [50], but not in Mexico [34]. The possibility that differences in sunlight and artificial light exposure might account for these urban-rural differences has not previously been considered [51, 52]. A number of studies have consistently found that, compared to individuals without an established psychiatric diagnosis, the spring seasonality of suicide is more pronounced in individuals with an established psychiatric diagnosis [53, 54], especially in individuals with a history of mood disorders [36, 55].…”
Section: Discussionmentioning
confidence: 94%
“…This rural increase has been found in France [6], Hungary [48], New Zealand [49], Sweden [49], and Austria [50], but not in Mexico [34]. The possibility that differences in sunlight and artificial light exposure might account for these urban-rural differences has not previously been considered [51, 52]. A number of studies have consistently found that, compared to individuals without an established psychiatric diagnosis, the spring seasonality of suicide is more pronounced in individuals with an established psychiatric diagnosis [53, 54], especially in individuals with a history of mood disorders [36, 55].…”
Section: Discussionmentioning
confidence: 94%
“…The observable difference is likely slightly exaggerated by the fact that the other two populations were younger than the Baependi one (average age 36.4 in London and 31.8 in São Paulo); however, this age difference is entirely insufficient to account for the major part of the variance (the London study indicates that the relationship between age and MEQ score corresponds to an average increase of 1 unit approximately every 3.8 years14). The difference in chronotype between rural and metropolitan populations is well known and have been described in human population samples living both in Brazil212223 and elsewhere2425, and even in songbirds26. The most obvious and likely strongest determinant of this difference is differential exposure to natural light during the day (particularly during the advancing window of the phase response curve) and artificial light (from indoor or outdoor sources) during the night (particularly during the delaying window of the phase response curve).…”
Section: Discussionmentioning
confidence: 99%
“…In industrialized societies where electrical lighting is abundant, exposure to sunlight during daytime is reduced, light exposure after sunset is increased, circadian timing is delayed, and endogenous circadian clock is less synchronized with the natural light–dark cycle relative to an environment with only natural light exposure (10). In addition, compared with individuals residing in rural areas, urban dwellers have less exposure to natural light and later sleep schedules (45). Apart from its effects on sleep timing, electrical lighting may also be a cause of insufficient sleep in industrialized societies (46).…”
Section: Discussionmentioning
confidence: 99%